A Simple In Vitro Model of Mechanical Injury of Confluent Cultured Endothelial Cells to Study Quantitatively the Repair Process - Klein-Soyer, Claude; Beretz, Alain; Millon-Collard, Régine; Abecassis, Joseph; Cazenave, Jean-Pierre (Thrombosis and Haemostasis, 1986)
A model of in vitro mechanical injury of confluent human endothelial cells (EC) in culture was developed. Human EC were obtained from umbilical veins and grown to confluence. Application on the EC monolayer of a calibrated disk of cellulose poly acetate paper resulted in removal of the EC, leaving a continuous subendothelial extracellular matrix (ECM) on the culture dish. The regeneration time depended on the original size of the lesion. Regeneration was similar with EC grown on different substrates such as human fibronectin, human subendothelial ECM, bovine collagen type I or surfaces coated with Transglutine®, a surgical glue containing adhesive proteins. A human brain extract containing growth factor activity accelerated significantly the repair of the lesion, especially at low serum concentration. This simple in vitro model of mechanical injury allows the quantitative study of the effects of matrices, growth factors and pharmacological agents on the repair process.
Keywords: Endothelium; Injury; Growth factor; Extracellular matrix-Pharmacology